2020
DOI: 10.3892/ijmm.2020.4735
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin 1 inhibits the apoptosis of human trophoblasts by activating the PI3K/Akt signaling pathway

Abstract: The excessive apoptosis of human trophoblasts can cause pregnancy-related diseases. It has been reported that fibronectin 1 (FN1) is closely associated with the invasion of human trophoblasts. The aim of the present study was to examine the effects of FN1 on the apoptosis of human trophoblasts and to investigate the underlying molecular mechanisms. It was found that FN1, a differentially expressed gene (DEG) in the GSE127170 dataset, was identified as the hub gene in a protein-protein interaction (PPI) network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
(39 reference statements)
1
31
0
Order By: Relevance
“…2n ). A number of key trophoblast regulators displayed significant chromatin accessibility changes consistent with reduced or increased expression in TEAD1 KO hTSCs, including ZFP57 58 , FN1 51 (downregulated), and CBR1 59 (upregulated) (Fig. 2o ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2n ). A number of key trophoblast regulators displayed significant chromatin accessibility changes consistent with reduced or increased expression in TEAD1 KO hTSCs, including ZFP57 58 , FN1 51 (downregulated), and CBR1 59 (upregulated) (Fig. 2o ).…”
Section: Resultsmentioning
confidence: 93%
“…There were 162 genes significantly downregulated in TEAD1 KO hTSCs ( p -adjust < 0.05) (Fig. 2l ), including many trophoblast regulators such as FOS 49 , 50 , FN1 51 , ITGB8 52 , MET 53 , and LOXL2 54 . Genes downregulated in TEAD1 KO hTSCs were enriched for GO terms such as integrin-mediated signaling pathway, regulation of TGF-β production, and regulation of cell motility (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FN1 was found to regulate activation of PI3K/AKT pathway in many diseases 23–25 . Thus, we intended to verify whether FN1 could regulate this signaling in BC.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the inhibitory action of LINC02381 depletion on cell process in BC was abrogated by FN1 overexpression. FN1 was a positive regulator of PI3K/AKT pathway in many diseases 23–25 . PI3K/Akt is a key intracellular pathway modulating many biological processes, including cell survival, apoptosis, and metastasis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative proteomics analyses revealed FN1 as a candidate biomarker of sporadic medullary thyroid cancer ( 36 ) and FN1 is also considered as a potential biomarker in OSCC regarding the tongue, mouth floor and edentulous ridge ( 15 ). Ji et al ( 37 ) revealed that the protein expression levels of Ki67 and PCNA is decreased by the silencing of FN1 in human trophoblasts. FN1 knockdown represses cell proliferation, invasion and migration of nasopharyngeal carcinoma cells, coupled with downregulated expression of MMP2 and MMP9 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%